Rules of The House: Family Law and Domestic Disputes in Colonial Korea: Book Review - Kania Hesty Kamarani (Presscience, 2024)
“Rules of the House: Family Law and Domestic Disputes in Colonial Korea” by Lim (2019), published by the University of California Press on November 13, 2018, provides a compelling examination of women's roles in civil courts during colonial Korea. The book focuses on the challenges women faced under Japanese family law, which was heavily influenced by patriarchal biases. Sungyun Lim, an Assistant Professor of Modern and Japanese History at the University of Colorado Boulder, argues that while Korean women struggled against patriarchal oppression, they were not passive victims. Instead, they proactively engaged with the Japanese colonial legal system to assert their rights. In turn, the Japanese used the rhetoric of progressive legal rights to further their colonial objectives. The book traces women’s civil disputes from the precolonial Choson dynasty, through the colonial era, and into the post-colonial reforms, offering a fresh perspective on Korean women’s legal struggles and their collaboration with the colonial state.